Combating Consumer Food Waste – An Exploration of Information Communication Technology Approach - John ADEBISI (Journal of Digital Food, Energy & Water Systems)
Existing food production and consumption rate especially from consumer’s point of view cannot be measured as viable due to varieties of social economic factors involved in the food supply chain. Combating food waste contributes extensively to food security measures and easing conservational burden thus improving justifiable consumption of food. Food waste emanating from consumers especially individual households is huge. A systematic approach to mitigate this is to creatively enlighten consumers as alertness and campaigns. However, literature reveals that complimentary initiatives are required to confront the problem of consumer waste. Information technology is comparatively new approach to lead consumers carefully using technical platforms and solutions in the right direction towards reducing food waste. This study tackles this research gap by conducting comprehensive reviews of articles pointing to food wastage prevention, weaknesses and potential usage of ICT tools for positive impacts on consumers to reduce food wastages. The study focuses on the use of ICT tools and techniques as a means to reduce food wastage. The reviews covered existing food wastage saving measures and applications (e.g. smart kitchen appliances, smart packaging and mobile applications). It further proposed a broad ICT driven food wastage avoidance framework that deals with the problem holistically. The framework shows how various levels of food supply chain can be integrated to tackle wastages from top to bottom in avoiding consumer wastage. However, future research is required to validate and build on this framework.